TINJAUAN YURIDIS TERHADAP PENGANGKATAN ANAK BERDASARKAN PENETAPAN PENGADILAN NEGERI BLORA SETELAH DIKELUARKANNYA UNDANG-UNDANG NOMOR 3 TAHUN 2006 TENTANG PERADILAN AGAMA - , INGGIL KATRIBAWANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of the research are to recognize the authority of District Court in prosecuting the plea concerning the removal of a child proposed by Islamic pleader following the validity of Law No. 3, 2006, as well as judgeâs consideration as the basic to approve a removal of a child case in District Court following the validity of the Law No. 3, 2006. The research concerning juridical review on removal of a child based on District Court Blora determination following the release of Law No. 3, 2006 is an juridical normative, that is a research using juridical law or norms product like legislation. To explain these, the researcher uses qualitative-descriptive method, which describes factual situation and condition happening amongst society, and then relate them with the valid law rules and correlate them with research substance. To collect primary and secondary data, some field and literature researches have been conducted. The results of this research are: (1) ) SEMA No. 2, 1979 about adoption, SEMA No. 6, 1983 SEMA No. 4, 1989, SEMA No. 3 Tahun 2005 about adoption, as has been arranged in the Guidance of Court tasks and administration in four environment justice court, then District Court still prosecute such cases. (2) Judgeâs basic consideration regarding removal of a child determination is juridical consideration includes : Law No. 4, 1979 concerning children welfare and Law No. 23, 2003, concerning children protection and sociological consideration includes: proof device proposed by the pleader,either in the form of document or witnessâ information which is conducted for the sake of the childâs interest and protection, as well as the guarantee concerning the future and legal status as a foster child.